Ketepatan Hasil dan Variasi Waktu Pendidihan Pemeriksaan Zat Organik - Haitami Haitami; Dinna Rakhmina; Syahid Fakhridani (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
The principle of organic substances determination in water samples is oxidized by an excess amount of KMnO4, then it is reduced excess amount of oxalic acid, the excess of oxalic acid is titrated back with KMnO4. Based on the procedures in ISO 06-6989.22-2004, a length of boiling time for organic substances determination in water samples is for 10 minutes. This study aimed to determine the effect of boiling time length to the accuracy of the organic substances determination result in water samples. This study was true experiment study with comparative study design. Samples were organic substances, specifically oxalic acid in distilled water in a concentration of 54 mg/L, which was examined for the organic substances level with a boiling time of 5, 10 and 15 minutes. The result on each boiling time length consecutively were 52,8 mg/L; 54,5 mg/L; dan 55,1 mg/L. The conclusion of the study was there was effect of boiling time length to the accuracy of organic substances determination result in water samples with the significance value of 0.002 (